Metacognition Profile on Habits of Mind in Biology Learning - Ilma Riksa Isfiani; Bambang Ekanara (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
The purpose of this study was to determine the level profile of the Thinking about Thinking (Metacognition) category in the habits of mind of high school students in Biology learning. The research method used is descriptive research. The sample selection technique used stratified random sampling technique. The population in this study were all students of class XI and XII at SMAN A, SMAN B, SMAN C, and SMAN D Bandung, as many as 294 students. Data collection used an instrument in the form of a Habits of Mind's Costa and Kallick questionnaire. The results showed that the metacognition profile of class XI students was 67% (299) and class XII students was 69% (307), which means that Thinking about Thinking (Metacognition) of high school students is included in the low category. This shows that high school students in class XI and XII have not fully demonstrated good metacognitive abilities. The results of this study indicate that the metacognition category in habits of mind still needs to be introduced and accustomed to school students, especially in learning biology.